North tunisian red slip ware from production sites in the salomonson survey (1960-1972) - HASENZAGL, CARINA (Bulletin antieke beschaving. Supplement, 2019)
This study addresses issues regarding the classification of African Red Slip Ware and the identification of different North Tunisian production centers by applying standardized fabric description an archaeological method to classify pottery according to the microscopic features of the sherd. It is based on survey finds from the North Tunisian workshops of Bordj el Djerbi, Henchir el Biar, Oudna and Pheradi Maius that were visited by the Dutch archaeologist J.W. Salomonson during survey campaigns in the 1960s and 1970s. The pieces from Salomonson's survey collection are of clear provenance and are therefore used to define the microscopic features of a production site.